Large-Scale Mapping of Transposable Element Insertion Sites Using Digital Encoding of Sample Identity. Issue 3 (1st March 2014) - Gohl, Daryl M; Freifeld, Limor; Silies, Marion; Hwa, Jennifer J; Horowitz, Mark; Clandinin, Thomas R
Abstract: Determining the genomic locations of transposable elements is a common experimental goal. When mapping large collections of transposon insertions, individualized amplification and sequencing is both time consuming and costly. We describe an approach in which large numbers of insertion lines can be simultaneously mapped in a single DNA sequencing reaction by using digital error-correcting codes to encode line identity in a unique set of barcoded pools.